2005
DOI: 10.1186/1477-9560-3-1
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: The use of antithrombotic agents and falls are independently associated with an increased risk of hemorrhagic injury. However, few studies have delineated the risk of fall-related hemorrhagic complications in persons who are taking antithrombotic therapy. The objective of this study was to compare the rates of fall-related hemorrhagic injury in hospital in-patients who are taking and not taking antithrombotic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“… 13 The mean age of patients with AF on treatment was much lower than the mean age of similar studies at a primary care setting. 7 , 14 The proportion of the male population on anticoagulation treatment was greater than females, similar to other studies done at tertiary care centers, 6 , 13 but there was a slight female preponderance at primary care centers. 7 …”
Section: Discussionsupporting
confidence: 84%
“… 13 The mean age of patients with AF on treatment was much lower than the mean age of similar studies at a primary care setting. 7 , 14 The proportion of the male population on anticoagulation treatment was greater than females, similar to other studies done at tertiary care centers, 6 , 13 but there was a slight female preponderance at primary care centers. 7 …”
Section: Discussionsupporting
confidence: 84%
“…In a number of studies, sensitivity of platelets to ADP and levels of this agonist in patients with AR revealed to be considerably amplified [ 25 , 85 ]. Moreover, in a randomized cross-over trial, patients with AR turned out to be highly responsive to platelet ADP receptor antagonist [ 86 ].…”
Section: Managementmentioning
confidence: 99%
“…It has been reported that 30–60% of patients can suffer venous events while 15–20% can suffer arterial events while bleeding manifestation is rare. 2 , 5 , 9 , 10 …”
Section: Discussionmentioning
confidence: 99%